Exploring short crack behaviour and fracture transition in 5052 aluminium alloy - Abdalrhaman Koko; Duaa Salim; Nathanael Leung; Nassos Spetsieris; Stan Smith; David England; Tan Sui; Tony Fry (Results in Engineering)
This study, employing in-situ scanning electron microscopy, electron backscatter diffraction, and digital image correlation, investigates the crack-length dependency of the quasi-brittle to ductile transition in 5052 aluminium alloy. A compact tension sample with {110} texture was examined, revealing crack propagation on (111¯) and (1¯11) transgranular cleavage planes and non-coherent paths under low-stress intensity factors (SIFs), with a maximum of 7.72 ± 0.09 MPa.m0.5 compared to the typical KIC of 25 MPa.m0.5. Crack growth was influenced by double-slip mechanisms and significant resistance at Σ33 grain boundaries. After crack arrest, SIFs derived from the local displacement field revealed a transition from microstructure-sensitive to nominal load-driven crack growth conditions.